Combination of nitrous oxide and the modified inflation‐deflation method for identifying the intersegmental plane in segmentectomy: A randomized controlled trial. Issue 9 (4th April 2021) - Yang, Wenjing; Liu, Zicheng; Yang, Chun; Liu, Shijiang; Guo, Minna; Wen, Wei; Wang, Jun; Liu, Cunming; Zhu, Quan
Abstract: Background: During thoracoscopic segmentectomy, accurately and rapidly identifying the intersegmental plane (ISP) is of great importance. This study aimed to investigate the effect and safety of a nitrous oxide (N2 O)/oxygen (O2 ) inspired mixture on the appearance time of the ISP (TISP ) via the modified inflation‐deflation method. Methods: A total of 65 participants who underwent segmentectomy were randomized into three groups: 75% N2 O ( n = 24), 50% N2 O ( n = 23) or 0% N2 O ( n = 18). The 75% N2 O group received a gas mixture of N2 O/O2 (Fio2 = 0.25), the 50% N2 O group received N2 O/O2 (Fio2 = 0.5), and the 0% N2 O group received 100% oxygen during lung expansion. The appearance time of satisfactory and ideal planes was recorded. Furthermore, arterial blood gas at breathing room air, one‐lung ventilation (OLV) before lung expansion, 5 and 15 min after lung expansion were also recorded. Results: TISP was significantly shorter in the 75% N2 O group (320.2 ± 65.9 s) compared with that of the 50% N2 O group (552.4 ± 88.9 s, p  < 0.001) and the 0% N2 O group (968.3 ± 85.5 s, p  < 0.001), while the 50% N2 O group was shorter than that of the 0% N2 O group ( p  < 0.001). Arterial oxygenation was significantly improved in the 0% N2 O group only after lung expansion, before which there were no differences in mean PaO2 values among groups. Conclusions: The use of N2 O in the inspired gas mixture during lung expansion is an applicable strategy to rapidly identify the ISP via the modified inflation‐deflation method without any adverse effect on OLV related arterial oxygenation during segmentectomy. Abstract : 1. A modified inflation‐deflation method is a simple technique for distinguishing the intersegmental demarcations. 2. Nitrous oxide is an inhaled anesthetic gas with high gas solubility, which could accelerate the process of lung collapse. 3. A combination of nitrous oxide and the modified inflation‐deflation method can quickly and accurately identify lung resection borders.